Gold-catalyzed cyclization of enediynes and arenediynes to 6H-benzo[c]chromen-6-one and dibenzo[c, h]chromen-6-one derivatives. Issue 8 (22nd February 2019) - Chen, Chin-Chau; Hsu, Chia-Ling; Wu, Ming-Jung
Abstract: The efficient synthesis of 6 H -benzo[ c ]chromen-6-one and dibenzo[ c, h ]chromen-6-one derivatives is described. Thus, treatment of arenediynes1 and enediynes5 with 5 mol % Ph3 PAuCl and 10 mol % of AgSbF6 in refluxing toluene gave dibenzo[ c, h ]chromen-6-ones4 and 6 H -benzo[ c ]chromen-6-ones6, in good yields, respectively. Graphical abstract: Image 1